Маркетингова комунікаційна політика: сутність та особливості на промисловому підприємстві - Ільченко, Тетяна Вікторівна; Ilchenko, Tetiana; Помазан, Ліна Миколаївна; Pomazan, Lina (Мукачівський державний університет, 2022)
В статті досліджено сутність та ключові особливості маркетингових комунікацій та маркетингової комунікаційної політики промислового підприємства. Розглянуто трактування сутності поняття комунікації в контексті промислового маркетингу. Досліджено ключові тенденції в системі маркетингових комунікацій підприємства. В статті проаналізовано специфічні ознаки маркетингових комунікацій. Встановлено, що дієвість маркетингових комунікацій та маркетингової комунікаційної політики в цілому безпосередньо залежить від індивідуальних ознак кожного суб’єкту системи маркетингу та використаних засобів комунікації. Встановлено, що систематичне вдосконалення маркетингової комунікаційної політики на промисловому підприємстві є запорукою здобуття стійкого іміджу і покращення позицій на профільних ринках збуту. The article examines the essence and key features of marketing communications and the marketing communications policy of an industrial enterprise. The interpretation of the essence of the concept of communication in the context of industrial marketing is considered. Key trends in the company's marketing communications system were studied. The article analyzes the specific characteristics of marketing communications. It was established that the effectiveness of marketing communications and marketing communication policy as a whole directly depends on the individual characteristics of each subject of the marketing system and the used means of communication. The dynamic development of modern society is accompanied by the presence of an information space that generates and improves the information infrastructure for the effective use of information resources. Ensuring sustainable competitive functioning of enterprises requires the application of a marketing communication policy adapted to the requirements of the modern dynamic macro-environment. Marketing communication policy, as a tool of effective management, is increasingly in demand in the practice of managing industrial enterprises. It has been established that the systematic improvement of the marketing communication policy at an industrial enterprise is the key to obtaining a stable image and improving positions in specialized sales markets. Speaking of all marketing tools that take part in ensuring a set of relationships and relationships, it is worth highlighting marketing communications, which generate a process of interaction with the target audience regarding the transmission of information about products and their properties and are able to maintain the connection of an industrial enterprise with consumers and stakeholders. Summarizing the results of the conducted research, it is worth emphasizing that effective communications with consumers in modern economic conditions are the basis for the success of any industrial enterprise. Marketing communication policy, in our opinion, can be characterized as a set of elements that unite all participants in communication, as well as means of transmitting and reproducing information.
Marketing communication policy: essence and features in an industrial enterprise
Keywords: маркетинг; marketing; маркетингові комунікації; marketing communications; маркетингова комунікаційна політика; marketing communication policy; промисловий маркетинг; industrial marketing; реклама; advertising; branding; брендинг